Sorting of complex sphingolipids within the cellular endomembrane systems - Svistunov, Victor O.; Ehrmann, Kigumbi J.; Lencer, Wayne I.; Schmieder, S. S. (Frontiers in Cell and Developmental Biology, 2025)
Cells contain a plethora of structurally diverse lipid species, which are unevenly distributed across the different cellular membrane compartments. Some of these lipid species require vesicular trafficking to reach their subcellular destinations. Here, we review recent advances made in the field that contribute to understanding lipid sorting during endomembrane trafficking.